Calcareous Nannofossils Events of Nephrolithus Frequens Zone to Markalius Inversus Zone in Section of Kazerun, Zagros (Iran) - Senemari, Saeedeh (International Journal of Geography and Geology, 2015)
One of the most complete Late Maastrichtian to Early Danian sequences contains the Kazerun section of West Fars Province, Zagros basin of Southwestern Iran. The present investigation identifies index species, 15 Genera and 22 Species of nannofossils in this boundary. Calcareous nannofossils, which observe in Cretaceous-Paleogene boundary strata, are believed to be appropriate means for biostratigraphical study. The majority of Cretaceous-Tertiary boundary (K/Pg) strata are made up of grey shale and then purple shale, respectively. The acquired nannofossils show continuity in K/Pg boundary in Western part of Fars Province. This agrees with the existence of Nephrolithus frequens zone, which predicts the age of late Late Maastrichtian and Markalius inversus zone which describes the age of Early Paleocene (Early Danian). Also, the examination of calcareous nannofossils of the Kazerun section at Zagros basin enabled us to recognize standard biozones defined in Mediterranean regions, especially Tethysian domain.